Blockchain adoption in financial auditing: A global perspective on the top public companies worldwide - Andoko, Michelle Princess; Natalia, Clara; Lindrianasari, Lindrianasari (Edelweiss Applied Science and Technology, 2025)
The persistent risks of data manipulation and operational inefficiencies within traditional, centralized audit systems pose a significant threat to the integrity of financial reporting. This study examines how the adoption of blockchain technology can address these limitations by improving three critical aspects of the audit process. Through a comprehensive empirical analysis, we demonstrate that blockchain integration significantly enhances audit quality by providing an immutable, transparent, and auditable ledger that mitigates the risk of human error and fraudulent activity. The automation of data collection and near-instantaneous verification simultaneously contribute to greater audit timeliness. Furthermore, the verifiable and cryptographic nature of blockchain-supported records establishes a trusted, single source of truth, which improves the quality of reported earnings by minimizing estimation bias and earnings management. These findings establish a clear case for blockchain as a foundational technology in modern auditing. This study offers crucial insights into how blockchain can benefit auditors and regulators, laying the groundwork for more robust and sustainable financial reporting practices.